Cost-Effectiveness Analysis of Sacubitril/Valsartan Compared to Enalapril for Heart Failure Patients in Indonesia - Zakiyah N; Sinuraya RK; Kusuma ASW; Suwantika AA; Lestari K (Dove Medical Press, 2021)
Neily Zakiyah,1,2 Rano K Sinuraya,1- 3 Arif SW Kusuma,2,4 Auliya A Suwantika,1,2,5 Keri Lestari1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 2Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, Indonesia; 3Unit of Global Health, Department of Health Sciences, University of Groningen, University Medical Center Groningen, Groningen, The Netherlands; 4Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, Indonesia; 5Center for Health Technology Assessment, Universitas Padjadjaran, Bandung, 40132, IndonesiaCorrespondence: Neily Zakiyah Tel/Fax +62 22-7796200Email neily.zakiyah@unpad.ac.idObjective: Sacubitril/valsartan is a relatively new medication that is more effective than the usual enalapril for heart failure patients with reduced ejection fraction. Therefore, this study aims to determine the cost-effectiveness of sacubitril/valsartan compared to enalapril in Indonesia's healthcare system.Methods: In this study, a Markov decision-analytic model was developed to estimate the total cost, health outcomes, and cost-effectiveness of sacubitril/valsartan compared to enalapril from Indonesia's healthcare perspective. The input parameters for the cost-effectiveness were predominantly from the PARADIGM-HF trial. Subsequently, the country-specific data were synthesized for medication and hospitalization costs, cardiovascular and non-cardiovascular death, as well as re-hospitalization rate. The incremental cost-effectiveness ratio (ICER) per quality-adjusted life years (QALYs) gained was estimated to determine the cost-effectiveness. Deterministic and probabilistic sensitivity analyses were conducted to assess the impact of parameter uncertainty.Results and Discussion: In the base case, sacubitril/valsartan was more costly and effective than enalapril with a total cost of IDR 91,783,325,865 (USD 6,487,522) vs IDR 68,101,971,241 (USD 4,813,653) and a total QALYs of 19,680 vs 18,795, resulting in an ICER of IDR 26,742,098 (USD 1890). Based on the willingness to pay threshold GDP per capita in Indonesia, it can be considered cost-effective. The most influential drivers of cost-effectiveness in deterministic sensitivity analysis were risk of mortality outside hospitalization, hospital admission rate, and cost of sacubitril/valsartan. The vast majority of simulation results from probabilistic analysis suggested that sacubitril/valsartan was likely resulted in higher cost and improved QALYs compared with enalapril, indicating the robustness of the model.Conclusion: Based on the current price in Indonesia, sacubitril/valsartan can be considered a cost-effective option, although this depends heavily on the willingness to pay threshold. Further studies that incorporate real-world evidence with sacubitril/valsartan are needed to inform the decision-making process.Keywords: cost-effectiveness, heart failure, Markov model, sacubitril/valsartan